SISTEM INVENTORI DAN PENGGAJIAN TOKO METRO ELEKTRONIK BERBASIS WEB DAN DESKTOP (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Metro Elektronik is a shop that selling various kinds of electronic goods such as refrigerator, air conditioner, television, etc. The current system that run in metro elektronik now has many flaws and reduce the overall performance of store mainly because of data integrity and inconsistency. Using php and java today I built a application that can help Metro Elektronik solve it’s problem.